Moral Panic Over Youth Violence: Wilding and the Manufacture of Menace in the Media - WELCH, MICHAEL; PRICE, ERIC A.; YANKEY, NANA (Youth & society, 2002)
In 1989, while reporting the well-publicized attack on a female jogger in New York City, the media discovered wilding, a newly stylized word used to describe sexual violence committed by a group of urban teens. Sociologically, the term wilding became particularly significant due to its racial connotation, perpetuating a stereotype of young Black (and Latino) males belonging to a dangerous class. This work explores the contours of moral panic over wilding by attending to elements of race, class, and fear of crime, especially as they manifest in the media. The findings contribute to a critical understanding of youth in society by offering an interpretation of wilding, a distinctive form of moral panic that symbolizes not only a threat to society at large but also to a political economy that reproduces racial and social disparities.